2017
DOI: 10.1038/srep45907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agomelatine on memory deficits and hippocampal gene expression induced by chronic social defeat stress in mice

Abstract: Chronic stress is known to induce not only anxiety and depressive-like phenotypes in mice but also cognitive impairments, for which the action of classical antidepressant compounds remains unsatisfactory. In this context, we investigated the effects of chronic social defeat stress (CSDS) on anxiety-, social- and cognitive-related behaviors, as well as hippocampal Bdnf, synaptic plasticity markers (PSD-95, Synaptophysin, Spinophilin, Synapsin I and MAP-2), and epigenetic modifying enzymes (MYST2, HDAC2, HDAC6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 77 publications
1
20
0
Order By: Relevance
“…Two‐stage SIT were employed to divide the CSDS into SUS and RES groups, as described in the literature 27 . The test consisted in two consecutive 2.5 minutes sessions, under low light conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Two‐stage SIT were employed to divide the CSDS into SUS and RES groups, as described in the literature 27 . The test consisted in two consecutive 2.5 minutes sessions, under low light conditions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, short‐ and long‐term reductions in the histone deacetylase (HDAC) levels (specifically HDAC 2), in the NAc and hippocampus have been observed in defeated mice. On the contrary, increases in histone acetyltransferase (HAT) activity have been described in the same structure (Covington et al., ; Martin et al., ; Montagud‐Romero, Montesinos et al., ). In addition, a downregulation of HDAC6 (in raphe neurons and in the hippocampus) and HDAC5 (in NAc and PFC) has been reported a few weeks after the last SD, changes that were reverted by the HDAC inhibitor imipramine (Espallergues et al., ; Fuchikami et al., ; Martin et al., ; Renthal et al., ).…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 98%
“…On the contrary, increases in histone acetyltransferase (HAT) activity have been described in the same structure (Covington et al., ; Martin et al., ; Montagud‐Romero, Montesinos et al., ). In addition, a downregulation of HDAC6 (in raphe neurons and in the hippocampus) and HDAC5 (in NAc and PFC) has been reported a few weeks after the last SD, changes that were reverted by the HDAC inhibitor imipramine (Espallergues et al., ; Fuchikami et al., ; Martin et al., ; Renthal et al., ). However, in a long‐term evaluation, the level of HDAC6 continued to be significantly elevated more than 1 month after the last agonistic encounter (Jianhua, Wei, Xiaomei, & Shao‐Hui, ), with an increase in the mRNA expression of different classes of HDAC enzymes in the PFC (Erburu et al., ).…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 98%
“…Kopschina Feltes and colleagues observed in Wistar rats that the effect of a similar RSD protocol was observed 1 week after RSD but was resolved after 90 days (Kopschina Feltes et al 2019). Martin and colleagues used a modified 10-day RSD protocol on C57BL mice and found that the transient effect of RSD had normalized after 18 days (Martin et al 2017). Gottschalk et al found that a 5-day RSD protocol has a significant effect on anhedonia 3 days after the last RSD exposure (Gottschalk et al 2018).…”
Section: Harmine Is Unable To Reverse Rsd -Induced Anxiety and Depresmentioning
confidence: 99%